Engineering Escherichia coli to increase triacetic acid lactone (TAL) production using an optimized TAL sensor-reporter system. (1st September 2018) - Li, Ye; Qian, Shuai; Dunn, Rachel; Cirino, Patrick C
Abstract: Triacetic acid lactone (TAL) (4-hydroxy-6-methyl-2-pyrone) can be upgraded into a variety of higher-value products, and has potential to be developed into a renewable platform chemical through metabolic engineering. We previously developed an endogenous TAL sensor based on the regulatory protein AraC, and applied it to screen 2-pyrone synthase (2-PS) variant libraries in E. coli, resulting in the identification of variants conferring up to 20-fold improved TAL production in liquid culture. In this study, the sensor-reporter system was further optimized and used to further improve TAL production from recombinant E. coli, this time by screening a genomic overexpression library. We identified new and unpredictable gene targets ( betT, ompN, and pykA ), whose plasmid-based expression improved TAL yield (mg/L/OD595 ) up to 49% over the control strain. This work further demonstrates the utility of customized transcription factors as molecular reporters in high-throughput engineering of biocatalytic strains.